2011
DOI: 10.3390/ph4111450
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Drug Design Using a Molecular Hybridization Approach

Abstract: The design of new drugs with better physiochemical properties, adequate absorption, distribution, metabolism, and excretion, effective pharmacologic potency and lacking toxicity remains is a challenge. Inflammation is the initial trigger of several different diseases, such as Alzheimer's disease, asthma, atherosclerosis, colitis, rheumatoid arthritis, depression, cancer; and disorders such as obesity and sexual dysfunction. Although inflammation is not the direct cause of these disorders, inflammatory processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…Alpha-Lipoic acid (α-LA, ALA) is a compound which is found in many prokaryotic and eukaryotic cell types and is formed naturally (1). α-LAhaspositive effectsonsomatic and autonomic neuropathies in diabetes, normalizes the endoneural blood flow, lowers oxidative stress and improves vascular dysfunction (2).…”
mentioning
confidence: 99%
“…Alpha-Lipoic acid (α-LA, ALA) is a compound which is found in many prokaryotic and eukaryotic cell types and is formed naturally (1). α-LAhaspositive effectsonsomatic and autonomic neuropathies in diabetes, normalizes the endoneural blood flow, lowers oxidative stress and improves vascular dysfunction (2).…”
mentioning
confidence: 99%
“…The development of new anti-inflammatory drugs via hybridization techniques through linking of new entities or mutual prodrugs has been used extensively in literature to obtain new compounds with better actions [7]. It is reported that a promising anti-inflammatory compounds were synthesized by condensation of salicylic acid carbohydrazide with substituted Isatin (Figure 8) [28].…”
Section: Discussionmentioning
confidence: 99%
“…In order to attain that goal, many approaches were used including hybridization techniques through linking of new entities or mutual prodrugs [7]. …”
Section: Introductionmentioning
confidence: 99%
“…If a toxicophore fragment of a given drug molecule does not overlap the pharmacophore, then it may be possible to redesign the molecule (32). For example, thalidomide derivatives devoid of teratogenic effects have been developed for treating chronic inflammation employing hybridization techniques, based on studies demonstrating that the teratogenicity is due to its distinct toxic subunit, glutarimide (33). PQ, an 8-aminoquinoline, has serious side effects and is known to induce hemolysis, especially in glucose-6-phosphate dehydrogenase (G6PD)-deficient individuals.…”
Section: Advantages Of Hybridsmentioning
confidence: 99%